Analysis of Social Perspectives in Reconstructing the History of Urbanization in Medan City - Lukitaningsih, Lukitaningsih; Swandhani, Ahmad Riyadi (JURNAL GEOGRAFI, 2024)
Urbanization is considered to be an ingrained social phenomenon in various large Indonesian cities, characterized by rapid urban population growth and drastic changes in social, economic and environmental structures. Urbanization in Indonesia shows a rapid increasing trend over the last few decades. Medan City, as one of the main urban centers in North Sumatra, has not escaped the impact of significant urbanization. Along with rapid economic and demographic growth, the city has experienced a major transformation in various aspects of city life. This research aims to identify the history of urbanization in Medan City from a social perspective. The research method used is a qualitative descriptive method through literature study sourced from journals, scientific articles, books and other relevant sources. The results of this research show that urbanization in Medan City has been going on for a long time. Strategically located on the east coast of Sumatra and between the confluence of the Deli River and the Babura River, Medan has vital trade access to the Malacca Strait. Especially in the period 2012 to 2022, the increase in population in Medan City occurred in almost all sub-districts. Of the 21 sub-districts, 17 sub-districts experienced an increase in population of more than 10%. Only one sub-district experienced a decline in population, namely Medan Baru Sub-district by 7.89%. The high level of urbanization in the city of Medan is generally caused by several factors, such as strategic location, the presence of natural resources (SDA), and supporting natural conditions. Meanwhile, the impact on society's social life includes rapid population growth, changes in societal structure, and social and cultural dynamics.Keywords: History, Urbanization, Social, Medan City